2010
DOI: 10.1021/ef100670z
|View full text |Cite
|
Sign up to set email alerts
|

Spray Combustion Characteristics and Gaseous Emissions of a Wood Derived Fast Pyrolysis Liquid-Ethanol Blend in a Pilot Stabilized Swirl Burner

Abstract: Biomass fast pyrolysis liquid (or bio-oil) is a cellulose based alternative fuel with the potential to displace fossil fuels in stationary heat and power applications. To better understand the combustion behavior and emissions of bio-oil, a 10 kW spray burner was designed and constructed. The effect of swirl, atomization quality, ignition source energy, air/fuel preheat, and equivalence ratio on the stability and emissions of bio-oil spray flames was investigated. A blend of 80% pyrolysis liquid and 20% ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(121 citation statements)
references
References 43 publications
3
116
0
Order By: Relevance
“…At elevated temperatures, the oil becomes increasingly reactive due to its high oxygen content. Secondly, the presence of water and components with a low boiling point can result in vapor formation in the fuel line at high oil temperatures [90,143]. Since these phenomena may lead to problems with the fuel supply, pyrolysis oil is generally preheated in the fuel line to a maximum temperature of 80-90 • C in order to avoid any undesired changes in physical and chemical state [32,67].…”
Section: The Application Of Pyrolysis Oil In Gas Turbinesmentioning
confidence: 99%
See 4 more Smart Citations
“…At elevated temperatures, the oil becomes increasingly reactive due to its high oxygen content. Secondly, the presence of water and components with a low boiling point can result in vapor formation in the fuel line at high oil temperatures [90,143]. Since these phenomena may lead to problems with the fuel supply, pyrolysis oil is generally preheated in the fuel line to a maximum temperature of 80-90 • C in order to avoid any undesired changes in physical and chemical state [32,67].…”
Section: The Application Of Pyrolysis Oil In Gas Turbinesmentioning
confidence: 99%
“…Solid matter can be formed inside the droplets during the evaporation process [31,126,143], which results in char particles that require long burnout times and potentially cause damage to certain turbine components. However, previous studies [31,126] showed that the charforming tendency of the droplets reduces with higher evaporation rates.…”
Section: The Application Of Pyrolysis Oil In Gas Turbinesmentioning
confidence: 99%
See 3 more Smart Citations